Tightening of tropical ascent and high clouds key to precipitation change in a warmer climate - Hui Su (Nature Portfolio, 2017)
The sensitivity of global precipitation to warming is largely governed by changes in atmospheric longwave radiation, a function of cloud cover. Here the authors show that tightening of the tropical circulation with warming drives a decrease in high cloud cover, resulting in higher precipitation changes.